Encephalitis and CSF increased level of interferon-α in Kikuchi–Fujimoto disease. (27th August 2012) - Guéguen, Antoine; Sené, Thomas; Maillart, Elisabeth; Gout, Olivier
Abstract : Neurological manifestations have been reported in Kikuchi–Fujimoto disease (KFD). Characteristics of brain lesions are not defined. In addition, no biological indexes are known to help clinicians along the diagnosis process. The authors describe encephalitis associated with KFD. Brain MRI, positron emission tomography (PET) scan and a large biological assessment including interferon α (INF-α) level measurement in cerebrospinal fluid (CSF) were performed. A 39-year-old man with chronic headaches developed diplopia, slow ideation and behavioural disturbances. MRI showed brain lesions particularly in the pontine region and internal temporal lobes with enhancement of the perivacular space and the walls of the lateral ventricle. The IFN-α level was increased in the CSF without viral infection. Cervical and mediastinal adenitis were evident as a hypermetabolic focus on a PET scan, and biopsy confirmed the diagnosis of KFD. The encephalitis spontaneously remitted. The authors characterised brain lesions especially related to KFD in association with increased of IFN-α level in the CSF.